PENGARUH NORMA SOSIAL JULO-JULO TENAGA KERJA TERHADAP KINERJA USAHATANI CABAI KOPAY DI KOTA PAYAKUMBUH - Revi Ernanda; Burhanuddin Burhanuddin; Joko Purwono (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
This paper is aimed to analyzing the effect of labor social norms named julo-julo on the performance of kopay chili farming in Payakumbuh city. Structural Equational Modelling-Partial Least Square (SEM-PLS) was used to analize the effect of social norm on the performance of kopay chili farming. The primary data used is taken through observation and interview process, meanwhile secondary data obtained from related institution. The selected samples were all 53 farmers of kopay chili in Payakumbuh City. The research results showed that thevariable of social norm has positif and significant effect on farmers’ performancewith the influence coefficient 0.317. The most dominant social norm that influence farming performance is providing aid to each other (λ) 0.894. Hence, government should be able to optimize social norm of julo-julo labor in desingning farming development strategies to improve the performance of kopay chili farming. Keywords: farming performance, partial least square (PLS), social norm